Analysis of Maisotsenko open gas turbine power cycle with a detailed air saturator model - Saghafifar, Mohammad (2015)
With ever increasing cost of fossil fuels and natural gas, the improvement in gas turbine power cycle efficiency is needed due to the tremendous savings in fuel consumption. Water/steam injection is considered as one of the most popular power augmentation techniques because of its significant impact on the gas turbine performance. One of the recently suggested evaporative gas turbine cycles is the Maisotsenko open cycle for gas turbine power generation. In this paper, detailed thermodynamic analysis of this cycle is investigated with a thorough air saturator model. A comparative analysis is carried out to signify the advantages and disadvantages of Maisotsenko gas turbine cycle (MGTC) as compared with humid air gas turbine cycles. MGTC performance is evaluated based on a simple recuperated gas turbine cycle. In addition, sensitivity analysis is performed to investigate the effect of different operating parameters on the overall cycle performance. Finally, integrating an air saturator instead of a conventional heat exchanger in recuperated gas turbine cycles enhances the power plant performance such that an efficiency enhancement of 7% points and net specific work output augmentation of 44.4% are obtained.